A prairie populist : the memoirs of Luna Kellie - Kellie, Luna (Singular lives., 1992)
Populist singer, Mid-Roader, editor, publisher, wife, mother of eleven, Luna Kellie was a well-informed, fervent member of the Farmers' Alliance movement in the latter part of the nineteenth century. Radicalized by railroad monopolies, corrupt government, recurring drought, heavy mortgages, and a desperate combination of rising costs and falling returns, prairie farmers were turning their energy toward raising ""less corn and more hell."" Kellie actively sought to organize Nebraska into cooperatives and educate rural people about land, transportation, and money reform. Her compelling, often he